PEMBUATAN BIOBRIKET DARI GAMBUT DAN AMPAS TEBU SEBAGAI SUMBER BELAJAR MATERI ILMU KIMIA DAN PERANANNYA - Lisa Mariati; yusbarina yusbarina (Konfigurasi : Jurnal Pendidikan Kimia dan Terapan, 2017)
AbstractHuman needs on fossil fuels is increasing, but the source is limited.  Thus, a renewable alternative source is needed.  One of them is Biomass.  Biomass fuel can be in the form of bio-briquette. Bio-briquette utilization as fuel is based on the carbon content contained in Biomass such as peat and bagasse.  This research aimed at knowing bio-briquette quality as fuel and learning source at senior high school.  Bio-briquette prepared with variation of peat and bagasse mass composition were 40: 0, 30: 10, 20: 20, 10: 30, 0: 40 (g: g).  Bio-briquette was made by using 20 g adhesive kanji.  Bio-briquette quality tested was done by testing the water content, ash content, volatile matter, fixed carbon, calorific value, and duration of flame.  Bio-briquette the best quality is the mass variation of G 10g: 30g AT with water content of 3.93%, ash content of 6.33%, volatile matter of 46.60%, fixed carbon of 43.14%, calorific  value of 5986 cal / g , duration of flame 210 minutes and the mass variation 0g G: 40g AT with water content of 2.33%, ash content of 3.83%, volatile matter of 49.47%, calorific value of 6198 cal / g, duration of flame 250 minutes. Preparing bio-briquette of peat and bagasse as learning source on chemistry material and its implementation was on the category of good (93.33%). Keywords: Bio-briquette, Peat, Bagasse, Quality test